Ad-hoc behavior in opportunistic radio - Gameiro, Atílio
The application of mathematical analysis to the study of wireless ad hoc networks has met with limited success due to the complexity of mobility, traffic models and the dynamic topology. A scenario based UMTS TDD opportunistic cellular system with an ad hoc behaviour that operates over UMTS FDD licensed cellular network is considered. In this paper, using an ah-hoc behavior in opportunistic Radio, we present how the overall system performance effect in terms of interference and routing.Therefore we develop a simulation tool that addresses the goal of analysis and assessment of UMTS TDD opportunistic radio system with ad hoc behaviour in coexistence with a UMTS FDD primary cellular networks.